PENGARUH DISIPLIN KERJA DAN KOMUNIKASI TERHADAP KINERJA GURU SMK NEGERI 2 OGAN KOMERING ULU - Rr. Dimas Veronica Priharti; Riza Susanti (STIE DWI SAKTI BATURAJA, 2020)
The purpose of this study is to research on Work Discipline and Communication on Teachers’ Performance at SMK Negeri 2 OKU. The analytical tool used is multiple linear regression. Based on the data analysis and partial discussion, the work discipline supports the performance of the teachers of SMK Negeri 2 OKU, with the results of T count (4,198)> T table (2,055), and communication increasing for the performance teachers of SMK Negeri 2 OKU, with the results of Tcount (3,433)> Ttable (2,055). And it works simultaneously on performance communication with SMK N 02 OKU teachers, with results calculated (70,935)> f table (3.37). The coefficient of determination (Adjusted R Square) shows the teacher's performance (Y) increases by 84.5% by working coordination variables (X1) and communication (X2) while receiving 15.5% produced by other variables not related in this study.